Characteristic Variation of Electromechanical Delay After the Botulinum Toxin Injection in Spastic Biceps Brachii Muscles - Chandra, Sourav; Afsharipour, Babak; Rymer, William Z.; Suresh, Nina L. (Frontiers in Neurology, 2022)
The objective of this study was to characterize the effects of intramuscular botulinum toxin (BT) injections on the electromechanical delay (EMD) in spastic human biceps muscles. The EMD is calculated as the time lag between muscle activation onset, as recorded from the surface electromyogram (sEMG), and the onset of recorded force. In a cohort of chronic stroke survivors, we compared the computed EMD derived from the spastic (injected) biceps brachii with that from the contralateral muscle. Eight participants were tested before and up to three months after a BT injection. At each session, participants followed an isometric trapezoidal force trajectory at 50% and 30% of the tested maximum voluntary contraction (MVC). Joint force and sEMG signals were recorded. The number of zero crossings (ZC) of the sEMG during the steady-state portion of the task was also computed. The EMD post-BT was found to increase by 64±10% (at 50%MVC) and 93±18% (at 30%MVC) when compared to pre-BT values, while the number of sEMG-ZC, the mean MVC values, and force-EMD slope exhibited striking reductions. These parameters calculated on the contralateral side remained relatively constant across sessions, with the EMD significantly lower and MVC values much higher. We discuss potential contributing factors to an increase in EMD values on the affected side, both pre and post BT. The observed co-variation across sessions of increased EMD values with decreased ZC estimates, a surrogate of motor outflow, and potentially more compliant muscle fascicles suggests that altered motor unit (MU) behavior contributes to the delayed force production, at least in part.